MARKETING STRATEGY ANALYSIS TO IMPROVE COMPETITIVENESS BAZNAS AND LAZNAS - Muhammad Furqan MD; Muhammad Zen (Sahabat Publikasi, 2023)
The marketing mix is a set of factors that are controlled to affect the demand for the company's output. An extraordinary combination suitable for making consumers aware of the company's products Companies using a marketing mix strategy with a mix of different elements Grouping The elements of the marketing mix are product (product), price (gift), location (location) and promotion (advertisement) ) According to LAZ NO law .23 of 2011 to Zakat Management said this: